Time for puppy school - O'Connor, Jane; Enik, Ted (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
When Frenchy gets in trouble one too many times, the Clancys decide it's time for puppy school.
OverDrive (READ) format features optional read-along narration.
105664
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Humorous fiction; Electronic books; Fiction; Juvenile works